From the privileged to the professionals - Curry, Graham, author.
1 online resource.
Keywords: "This book is concerned with the early years of the Football Association Challenge Cup, examining events from its inception in 1871-2 to the beginning of the Football League in 1888-9. The work is underpinned by the figurational sociology of Norbert Elias, employing his ideas around the European 'civilising process', power and lengthening chains of human interdependency. Most of all, the majority of the text has been compiled using primary source material such as newspaper reports and the minutes of the Football Association, which encourages original and unique additions to the body of knowledge. There exist no comparable offerings on the time period involved, with the book providing a distinct perspective for scholars and non-specialists alike. The initial years of the competition were dominated by teams consisting mainly of upper middle class southern amateurs. However, by the early 1880s, they were supplanted by men who were initially covert and, eventually, overt professionals, many of whom hailed from Scotland, but mainly represented clubs from Lancashire and the West Midlands. The FA Cup, despite losing some of its allure when compared to competitions such as the UEFA Champions League, still retains a magic of its own in the English football calendar"--